Ubuntu powerful hacks and customizations - Krawetz, Neal (Indianapolis, IN Wiley Pub, 2010)
A guide to Ubuntu covers such topics as customizing the user environment, configuring devices, managing software, tuning processes, collaborating, multitasking applications, and securing the system
Optimizing your system. Hacking the installation ; Customizing the user environment ; Configuring devices ; Adapting input devices -- Working with compatibility. Managing software ; Communicating online ; Collaborating -- Improving performance. Tuning processes ; Multitasking applications ; Getting graphical with video bling -- Securing your system. Locking down Ubuntu ; Advanced networking ; Enabling services
Includes index
1 14
GENR_KNOWL, NEW
Keywords: Linux (Computer software); Ubuntu (Electronic resource); Ubuntu (Electronic resource); Computer operating systems; Operating systems (Computers)